2007
DOI: 10.1038/sj.eye.6702924
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for retinopathy of prematurity in very low and in extremely low birth weight infants in a unit-based approach in southern Brazil

Abstract: Aims To analyse the incidence and risk factors for retinopathy of prematurity (ROP) and survival rates among extremely low birth weight (ELBW) and very low birth weight (VLBW) preterm infants. Methods A prospective cohort study of 352 infants admitted at a teaching hospital, Hospital de Clinicas de Porto Alegre, Brazil, between October 2002 and December 2006, was screened for ROP. The ELBW group comprised infants whose birth weight (BW) was p1000 g and the VLBW group comprised those infants whose BW were 41000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 34 publications
6
47
1
6
Order By: Relevance
“…In Brazil, these scoring systems have become increasingly important considering survival rates, especially among VLBW and extremely low-BW preterm babies (babies with BW <1,000 g), because the Brazilian survival rates are lower than those reported in industrialized countries [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, these scoring systems have become increasingly important considering survival rates, especially among VLBW and extremely low-BW preterm babies (babies with BW <1,000 g), because the Brazilian survival rates are lower than those reported in industrialized countries [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…According to the Brazilian guidelines for ROP screening, we also included in this study all babies with BW >1,501 g but with GA ≤32 weeks at birth (estimated by the New Ballard method for newborns with obstetric GA up to 34 weeks) [10, 11]. Pupils were dilated with tropicamide 0.5% and phenylephrine 2.5% eyedrops, instilled 1 h before examination.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown in a number of studies that extreme prematurity plus multiple hits of perinatal inflammation appear to be involved in ROP etiology and progression [26,39]. Again, lower GA and birth weight are associated with increased oxygen therapy, which is an independent risk factor for development of ROP [80]. In a recent meta-analysis by Saugstad and Aune [81], it was found that a lower oxygen saturation targeting by pulse oximetry reduced severe ROP by 50%, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Embora esses importantes estudos brasileiros, baseados em dados de unidades neonatais isoladas, sejam da década passada e, portanto, anteriores à publicação das diretrizes brasileiras para a detecção da ROP, a prevalência da doença em nossa instituição foi inferior ao relatado por aqueles autores. Em estudo anteriormente publicado (19) , verificamos a prevalência de 48,9% de ROP em qualquer estadiamento, quando analisamos apenas os pré-termos com PN <1.000 gramas, e que essa prevalência fica reduzida a apenas 18,2% de ROP em qualquer estadiamento, se considerarmos somente os pacientes com PN >1.000 gramas. Estudo recente, publicado por Bonotto et al (20) , em 2007, mostrou dados sobre 286 prematuros atendidos no período entre 1992 e 1999, na cidade de Joinville em Santa Catarina.…”
Section: Discussionunclassified